FilmArray® Meningoencephalitis panel in the diagnosis of central nervous system infections: stewardship and cost analysis in a paediatric hospital in Chile - Mirta Acuña; Dona Benadof; Karla Yohannessen; Yennybeth Leiva; Pascal Clement (BMC, 2022)
Abstract Background Central nervous system (CNS) infection has been an ongoing concern in paediatrics. The FilmArray® Meningoencephalitis (FAME) panel has greater sensitivity in identifying the aetiology of CNS infections. This study's objective was to compare the aetiological identification and hospitalization costs among patients with suspected CNS infection before and after the use of FAME. Methods An analytical observational study was carried out using a retrospective cohort for the pre-intervention (pre-FAME use) period and a prospective cohort for the post-intervention (post-FAME use) period in children with suspected CNS infection. Results A total of 409 CSF samples were analysed, 297 pre-intervention and 112 post-intervention. In the pre-intervention period, a total of 85.5% of patients required hospitalization, and in the post-intervention period 92.7% required hospitalization (p < 0.05). Median of ICU days was significantly lower in the post-intervention period than it was in the pre-intervention period. The overall positivity was 9.4 and 26.8%, respectively (p < 0.001). At ages 6 months and below, we found an increase in overall positivity from 2.6 to 28.1%, along with an increased detection of viral agents, S. agalactiae, S. pneumoniae, and N. meningitidis. The use of this diagnostic technology saved between $2916 and $12,240 USD in the cost of ICU bed-days. FAME use provided the opportunity for more accurate aetiological diagnosis of the infections and thus the provision of adequate appropriate treatment. Conclusions The cost/benefit ratio between FAME cost and ICU bed-day cost savings is favourable. Implementation of FAME in Chilean public hospitals saves public resources and improves the accuracy of aetiological diagnosis.